ABNORMAL MICROFAUNAL SHELLS AS EARLY WARNING INDICATOR OF ENVIRONMENTAL CHANGES SURROUNDING BERAU DELTA, EAST KALIMANTAN - Kresna Tri Dewi; Yusuf Adam Priohandono (BULLETIN OF THE MARINE GEOLOGY, 2011)
A total of 25 sediment samples from surrounding Berau Delta, East Kalimantan have been used for microfaunal study. It is found some abnormal shells of ostracoda, foraminifera and other forms with darkish shells (black, dark green and dark brown). These forms were analyzed using SEM-Energy Dispersive X-ray spectroscopy (EDX or EDS) to know their chemical composition. The result shows that these abnormal forms composed of CaO, SiO2, C, FeO, Al2O3, K2O, and small amount of Na2O and Cl. They may derive from different sources: CaO and MgO from neutralized component during the environmental management to handle the Acid Mine Drainage (AMD). The other components may derive from coal ash during combustion process or other activities. From this result, the small amount (less than 5%) of abnormal shells may be used as early warning indicator of environmental changes in the study area. Keywords: abnormal microfaunal shells, chemical composition, Berau Delta. Sebanyak 25 sampel sedimen dari sekitar Delta Berau, Kalimantan Timur telah digunakan untuk studi mikrofauna. Ditemukan cangkang abnormal dari ostracoda, foraminifera dan spesimen bentuk lain dengan cangkang kegelapan (hitam, hijau tua dan coklat tua) Bentuk-bentuk ini kemudian dianalisa menggunakan SEM-Energy Dispersive X-ray spectroscopy (EDX or EDS) untuk mengetahui komposisi kimiawinya. Hasilnya menunjukkan bahwa cangkang-cangkang mikrofauna yang abnormal ini mengandung CaO, SiO2, C, FeO, Al2O3, K2O, dan sedikit kandungan Na2O dan Cl. Komponen ini kemungkinan mempunyai sumber yang berbeda: CaO dan MgO mungkin berasal dari bahan penetral selama pengelolaan lingkungan untuk mengatasi air asam tambang (AMD). Komponen lain berasal dari abu batubara saat proses pembakaran atau aktivitas lain. Jumlah cangkang abnormal yang sedikit (kurang dari 5%) ini kemungkinan dapat digunakan sebagai indikator peringatan dini adanya perubahan lingkungan di daerah penelitian. Kata kunci: cangkang mikrofauna abnormal, komposisi kimiawi, Delta Berau